2012
DOI: 10.1016/j.socscimed.2012.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging health capital at the workplace: An examination of health reporting behavior among Latino immigrant restaurant workers in the United States

Abstract: This article examines the choices made by a sample of Latino immigrant restaurant workers in regard to their health management, particularly in response to illness and injury. I draw on 33 interviews with kitchen staff employed in the mainstream restaurant industry in San Jose, California, and Houston, Texas, in 2006 and 2007. I argue that workers must consider complex power relationships at work in weighing the advantages of calling in sick, using protective equipment, seeking medical care, or filing a worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…On the one hand, they are deportable "aliens, " and employers who hire them are subject to fines and criminal prosecution. On the other hand, they are a critical part of the workforce, and as easy targets for abuse, they also are an important outreach priority for labor standards enforcement agencies and advocates (Gleeson 2012a). The government then is at once responsible for policing and aiding undocumented workers.…”
Section: Precarit Y and Power In A Global Ec Onomymentioning
confidence: 99%
See 3 more Smart Citations
“…On the one hand, they are deportable "aliens, " and employers who hire them are subject to fines and criminal prosecution. On the other hand, they are a critical part of the workforce, and as easy targets for abuse, they also are an important outreach priority for labor standards enforcement agencies and advocates (Gleeson 2012a). The government then is at once responsible for policing and aiding undocumented workers.…”
Section: Precarit Y and Power In A Global Ec Onomymentioning
confidence: 99%
“…My previous work examined how workers develop a legal consciousness about their rights and identified what factors keep them from coming forward with a claim (Gleeson 2010). The concept of legal consciousness has become somewhat shopworn in the field of law and society, but it is still useful for understanding how laws sustain their institutional power and how individuals understand their rights under the law and make decisions as to whether and how to exercise them (Silbey 2005(Silbey , 2008).…”
Section: Legal C Onsciousness and Deportabilit Ymentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence shows that unauthorized workers suffer significantly higher rates of workplace violations than do US-born and authorized immigrants (Bernhardt, Spiller, and Theodore 2013). Studies have also detailed how unauthorized status inhibits workers' ability to file claims against their employers when faced with workplace rights abuses (Gleeson 2010(Gleeson , 2012. Finally, Hall, Greenman, and Farkas (2011) found that unauthorized workers do not reap the same rewards for schooling and their wages grow more slowly in comparison to their authorized counterparts.…”
mentioning
confidence: 99%